Perceived Personal Cost and Whistleblowing Intention: Testing a Multi-Moderation Model - Tito IM. Rahman Hakim; Prasetyono Prasetyono; Rifki Aprillah Saleh; Ravid Nur Wahid (Jurnal Akuntansi dan Bisnis, 2025)
This study aims to investigate the relationship between accounting students' intentions to report wrongdoing and their perceptions of personal cost. Additionally, this article examines how the microsocial ethical environment, group cohesion, and peer-reporting type moderate the effect of perceived personal cost on whistleblowing intentions. The study employs data collected from 182 students at three state universities in Madura. Participants were selected using a convenient non-probability sampling method and were administered a questionnaire. The data were analyzed using SmartPLS version 4. The results indicate that perceived personal cost has a positive influence on whistleblowing intentions, supporting the prosocial behavior argument. Regarding the interaction effects, the findings reveal that the microsocial ethical environment fails to moderate the main effect (perceived personal cost on whistleblowing intentions), while group cohesion and peer-reporting type partially moderate the main effect. These findings extend the existing theory regarding whistleblowing and are valuable in assisting universities in formulating whistleblowing systems that are customized to accommodate students' fraud reporting.